An improvement in the design process of sustainable peak power rating transformer for solar utility - Emir Yükselen; Ebrahim Rahimpour (International Journal of Electrical Power & Energy Systems)
The transformer industry faces critical challenges, such as maintaining reliable production while meeting rising sustainability requirements. This paper introduces a significant advancement in the design and optimization of a transformer dedicated to a photovoltaic power plant, which exhibits a unique loading cycle distinct from standard power and distribution transformers. The main aim is to minimize the carbon footprint by enhancing the design process to improve operational performance, efficiency, and functional reliability. Such upgrades are essential for transitioning to a zero-emission electricity system and developing green energy projects.In this paper, a transformer has been studied using a combination of electrical design and 3D finite element method simulation to evaluate various design parameters. An optimization study has been conducted using an innovative multi-objective genetic algorithm utilizing a cost function that factors in size and material costs to identify the most efficient and cost-effective design solutions.The proposed design method was then validated through thermal model simulations and experimental tests based on the photovoltaic load cycle. A comparison of critical thermal parameters directly affecting the transformer’s lifetime and reliability was also drawn. The results were consistent with the expected outcomes, confirming the effectiveness and reliability of the proposed design methodology.